Dissecting the paradoxical effects of hydrogen bond mutations in the ketosteroid isomerase oxyanion hole - Kraut, Daniel A. (National Academy of Sciences, 2010)
The catalytic importance of enzyme active-site interactions is frequently assessed by mutating specific residues and measuring the resulting rate reductions. This approach has been used in bacterial ketosteroid isomerase to probe the energetic importance of active-site hydrogen bonds donated to the dienolate reaction intermediate. The conservative Tyr16Phe mutation impairs catalysis by 10(5)-fold, far larger than the effects of hydrogen bond mutations in other enzymes. However, the less-conservative Tyr16Ser mutation, which also perturbs the Tyr16 hydrogen bond, results in a less-severe 10(2)-fold rate reduction. To understand the paradoxical effects of these mutations and clarify the energetic importance of the Tyr16 hydrogen bond, we have determined the 1.6-Å resolution x-ray structure of the intermediate analogue, equilenin, bound to the Tyr16Ser mutant and measured the rate effects of mutating Tyr16 to Ser, Thr, Ala, and Gly. The nearly identical 200-fold rate reductions of these mutations, together with the 6.4-Å distance observed between the Ser16 hydroxyl and equilenin oxygens in the x-ray structure, strongly suggest that the more moderate rate effect of this mutant is not due to maintenance of a hydrogen bond from Ser at position 16. These results, additional spectroscopic observations, and prior structural studies suggest that the Tyr16Phe mutation results in unfavorable interactions with the dienolate intermediate beyond loss of a hydrogen bond, thereby exaggerating the apparent energetic benefit of the Tyr16 hydrogen bond relative to the solution reaction. These results underscore the complex energetics of hydrogen bonding interactions and site-directed mutagenesis experiments.